Development of Circular Economy Concept: Historical Background - Maksymiv, Yuliia; Yakubiv, Valentyna; Hryhoruk, Iryna; Kravtsiv, Viktoriia (Journal of Vasyl Stefanyk Precarpathian National University, 2021)
Nowadays, sharp economic growth has increasingly depended on utilizing different resources causing environmental issues and hindering sustainable development. Consequently, governments of developed countries, the public sector, representatives of business structures, and scientists look at the circular economy as a way to support achieving sustainable development goals. The article aims at researching the historical background of the development of circular economy, analyzing the basic approaches and their possible usage for spreading this concept in developing countries, such as Ukraine. It is mentioned that the concept of circular economy cannot be traced back to a single author or date when it appeared. The concept of circular economy was inspired by several schools of thought with overlapping approaches, which demonstrates the relevance of distinguishing evolutionary phases and framings of a concept. The article presents a historical overview of the development of the concept of circular economy since the 1960s. The stages of adoption of regulations in the EU in the field of promoting the transition to a circular economy are highlighted, key milestones and key actions that actively began in 2015 and continue to this day, are described. This positive experience should be taken as a basis in developing countries, where the circular economy is in its infancy. The article also analyzes the highly cited scientific papers in the Scopus Scientometric Database and the basic definitions of the concept of "circular economy". Our findings indicate that the circular economy necessitates a systemic shift in the state policy of Ukraine, as well as economic science, and it should be aimed at developing a clear strategy and improving basic regulations in this area to increase the social responsibility of both businesses and local communities. The growth of a circular economy will benefit everyone within the limits of this planet.